REVITALIZING SPORTS CENTERS TO INCREASE PUBLIC AWARENESS OF THE IMPORTANCE OF HEALTH - Adi, Agung Nugroho; Santoso, Dwi Budi; Wijaya, Anorti Ika; Rahmawati, Rahmawati (Universitas Islam Malang, 2024)
Community welfare can be measured from the level of community health. To create a healthy community, adequate facilities, infrastructure and infrastructure are needed, namely by establishing a sports center. The sports center at Pesanggrahan Pratama Housing has long been neglected due to lack of maintenance. The purpose of this community service program is to revitalize the neglected sports center at Pesanggrahan Pratama Housing so that it can be used properly for sports activities and to socialize the importance of healthy life. The method of implementing community service consists of three stages including preparation, implementation and evaluation. The result of this service is the formation of a sports center with a new face and sports activities of residents can be seen in the morning and evening. Based on the results of the evaluation and monitoring using the Guttman scale, it shows that the revitalized sports center and the socialization of the importance of healthy life have a significant impact on residents. Residents start exercising and living a healthy life. So that this community service program is successful and has a positive and sustainable impact on residents of Pesanggrahan Pratama Housing.